Multiple-image encryption with bit-plane decomposition and chaotic maps. (May 2016) - Tang, Zhenjun; Song, Juan; Zhang, Xianquan; Sun, Ronghai
Abstract: Image encryption is an efficient technique of image content protection. In this work, we propose a useful image encryption algorithm for multiple grayscale images. The proposed algorithm decomposes input images into bit-planes, randomly swaps bit-blocks among different bit-planes, and conducts XOR operation between the scrambled images and secret matrix controlled by chaotic map. Finally, an encrypted PNG image is obtained by viewing four scrambled grayscale images as its red, green, blue and alpha components. Many simulations are done to illustrate efficiency of our algorithm. Highlights: We propose an efficient algorithm for multiple-image encryption. Our algorithm can convert four grayscale images to a single encrypted PNG image. Our algorithm can accurately reconstruct original images from the encrypted PNG image.